A comparison of microelectrodes for a visual cortical prosthesis using finite element analysis - Brunton, Emma K.; Lowery, Arthur J.; Rajan, Ramesh (Frontiers in Neuroengineering, 2012)
Altering the geometry of microelectrodes for use in a cortical neural prosthesis modifies the electric field generated in tissue, thereby affecting electrode efficacy and tissue damage. Commonly, electrodes with an active region located at the tip (“conical” electrodes) are used for stimulation of cortex but there is argument to believe this geometry may not be the best. Here we use finite element analysis to compare the electric fields generated by three types of electrodes, a conical electrode with exposed active tip, an annular electrode with active area located up away from the tip, and a striped annular electrode where the active annular region has bands of insulation interrupting the full active region. The results indicate that current density on the surface of the conical electrodes can be up to ten times greater than current density on annular electrodes of the same height, which may increase the propensity for tissue damage. However choosing the most efficient electrode geometry in order to reduce power consumption is dependent on the distance of the electrode to the target neurons. If neurons are located within 10 micrometers of the electrode, then a small conical electrode would be more power efficient. On the other hand if the target neuron is greater than 500 micrometers away – as happens normally when insertion of an array of electrodes into cortex results in a “kill zone” around each electrode due to insertion damage and inflammatory responses - then a large annular electrode would be more efficient.